Conformational analysis of 2-substituted cyclohexanone ketal derivatives by molecular mechanics and nuclear magnetic resonance - Varnalı, Tereza. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
The present study is concerned with the application of the Molecular Mechanics Method to 2-substituted cyclohexanoneketals. The object is to find the conformational free energy difference between the equilibrating conformers and to compare the theoretical results to those found experimentally. For the application of molecular mechanics, models of the compounds underinvestigation were described, the inter-atomic distances and angles were computed, the most important interactions were determined and the parameters needed for calculations of the interactions and functions relating parameter to energy were chosen. First, molecular mechanics was applied to spiro- [5,4]-1-halo-6,9-dioxodecane (1 in Fig. 1.1.1) and spiro-[5,5]-1-halo-6, 10-dioxoundecane(2 in Fig.1.1.1) where the halogen was chlorine or bromine. The results obtained theoretically showed preference for the conformer bearing the axialhalogen in (2) system and the conformer bearing the equational halogenin (1) system, being in accordance to experimental results reported by Zefirovet et. al. Secondly, molecular mechanics was applied to spiro- [5,4]-1-halo-6,9-dioxodecane and spiro-[5,5]-1-nitro-6,10 undecane and the results obtained theoretically in contrast to halogens, showed preference for the conformation in which the nitro group is equatorial in both cases ( 1 ) and ( 2 ). Finally, the 4-t-butyl derivatives of the nitro-(1) and (2) systems, and the (1) and (2) systems were synthesized and the free energy difference between the equilibrating conformers were obtained experimentally using NMR parameters. Experimental results were in parallel to those found theoretically. In previous studies the nitro group has been shown to behave differently than halogens and similar groups due to its electronic distribution, size, structure and formal change. The unique behavior of the nitro group has been shown once more both theoretically and experimentally.
Keywords: Conformational analysis.; Nuclear magnetic resonance.